Unraveling Ocyptamus and the Baccha legacy (Diptera: Syrphidae): redefinition of groups and new species descriptions - Mengual, Ximo; Miranda, Gil Felipe G.; Thompson, F. Christian (Zootaxa, 2018)
The systematics of Ocyptamus sensu lato has been reviewed, its species groups redefined, and some taxa resurrected. These and other related taxa are diagnosed to aid in distinguishing between them. The status of the following genera is revised: Calostigma Shannon stat. rev., Hermesomyia Vockeroth stat. rev., Hybobathus Enderlein stat. rev., Mimocalla Hull stat. rev., Orphnabaccha Hull stat. rev., Pipunculosyrphus Hull stat. rev., Pseudoscaeva Vockeroth stat. rev., and Styxia Hull stat. rev. New species of the Neotropical genus Ocyptamus are described from Costa Rica and Venezuela: Ocyptamus maximus Thompson sp. nov., Ocyptamus myiophagus Thompson sp. nov., and Ocyptamus megafemur Thompson sp. nov. In addition, an identification key for the genera and species groups of Ocyptamus sensu lato is provided, as well as a redescription of Syrphus sargoides Macquart.Lectotypes are designated for Doros disjuncta Sack, Baccha placiva Williston, Baccha pulla Sack, Ocyptamus funebris Macquart, Syrphus sargoides, and Syrphus immaculatus Macquart. Moreover, Syrphus immaculatus Macquart is considered to be a species of the genus Toxomerus, and new species synonyms are also given: Baccha atypica Curran is a junior synonym of Syrphus conjunctus Wiedemann; Baccha flata Hull and Doros disjuncta Sack are jun. syn. of Syrphus sargoides Macquart; Baccha bromleyi Curran is a jun. syn. of Ocyptamus funebris Macquart; Baccha sepia Hull, Baccha danaida Hull, Baccha violacea Hull, and Baccha ursula Hull are all synonyms of Ocyptamus pullus (Sack); Baccha nerissa Hull is a jun. syn. of Pelecinobaccha hiantha (Hull); and Baccha panamensis Curran is a jun. syn. of Pelecinobaccha transatlantica (Schiner).